y(25+-.75y)=350

Simple and best practice solution for y(25+-.75y)=350 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y(25+-.75y)=350 equation:


Simplifying
y(25 + -0.75y) = 350
(25 * y + -0.75y * y) = 350
(25y + -0.75y2) = 350

Solving
25y + -0.75y2 = 350

Solving for variable 'y'.

Reorder the terms:
-350 + 25y + -0.75y2 = 350 + -350

Combine like terms: 350 + -350 = 0
-350 + 25y + -0.75y2 = 0

Begin completing the square.  Divide all terms by
-0.75 the coefficient of the squared term: 

Divide each side by '-0.75'.
466.6666667 + -33.33333333y + y2 = 0

Move the constant term to the right:

Add '-466.6666667' to each side of the equation.
466.6666667 + -33.33333333y + -466.6666667 + y2 = 0 + -466.6666667

Reorder the terms:
466.6666667 + -466.6666667 + -33.33333333y + y2 = 0 + -466.6666667

Combine like terms: 466.6666667 + -466.6666667 = 0.0000000
0.0000000 + -33.33333333y + y2 = 0 + -466.6666667
-33.33333333y + y2 = 0 + -466.6666667

Combine like terms: 0 + -466.6666667 = -466.6666667
-33.33333333y + y2 = -466.6666667

The y term is -33.33333333y.  Take half its coefficient (-16.66666667).
Square it (277.7777779) and add it to both sides.

Add '277.7777779' to each side of the equation.
-33.33333333y + 277.7777779 + y2 = -466.6666667 + 277.7777779

Reorder the terms:
277.7777779 + -33.33333333y + y2 = -466.6666667 + 277.7777779

Combine like terms: -466.6666667 + 277.7777779 = -188.8888888
277.7777779 + -33.33333333y + y2 = -188.8888888

Factor a perfect square on the left side:
(y + -16.66666667)(y + -16.66666667) = -188.8888888

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| x^2+y^2+6x-14y+42=0 | | 42-21x=63-7y | | (6xy+7)dx+(3x^2-2)dy=0 | | 6x+9-x+19= | | 4x+10=-42-8x | | 3n=34 | | 17x-2x=7x+11 | | 7x+13=3x+65 | | 4x+38=180 | | 2(x-3)(x-3)+3=13 | | 2(x-3)+3=13 | | x^4-x^3-2x^2+4x-24=0 | | (X^2+24)= | | 3x^2-11x-3=-x^2 | | Un=5+(0.1n-0.1) | | Un=5+(0.1n+0.1) | | Cos(5x)-cos(9x)=0 | | z^2-(3-2i)z+(5-5i)=0 | | 6x=n+4 | | 4x^2+12x+9=49x | | 4x^3+12x+9=49x | | -6.8(7.9+1.2*-7.3)+3.7=4.2*-7.3+40.90016 | | 1/8+2/3= | | 1/3+2/3= | | 5y+11=6 | | -6.8(7.9+1.2x)+3.7=4.2x+40.90016 | | x^2-1x+40=0 | | (m+2n+1)(m-n+2)=5 | | x^2+12x+35x=0 | | 4x+13=-29-2 | | x+2x+6x+18x=160 | | 7(x*5)=9(6+4) |

Equations solver categories